The Role of Tissue Factor In Signaling Pathways of Pathological Conditions and Angiogenesis - Heidari, Zahra; Naeimzadeh, Yasaman; Fallahi, Jafar; Savardashtaki, Amir; Razban, Vahid; Khajeh, Sahar (Current molecular medicine, 2024)
Tissue factor (TF) is an integral transmembrane protein associated with the extrinsic coagulation pathway. TF gene expression is regulated in response to inflammatory cytokines, bacterial lipopolysaccharides, and mechanical injuries. TF activity may be affected by phosphorylation of its cytoplasmic domain and alternative splicing. TF acts as the primary initiator of physiological hemostasis, which prevents local bleeding at the injury site. However, aberrant expression of TF, accompanied by the severity of diseases and infections under various pathological conditions, triggers multiple signaling pathways that support thrombosis, angiogenesis, inflammation, and metastasis. Protease-activated receptors (PARs) are central in the downstream signaling pathways of TF. In this study, we have reviewed the TF signaling pathways in different pathological conditions, such as wound injury, asthma, cardiovascular diseases (CVDs), viral infections, cancer and pathological angiogenesis. Angiogenic activities of TF are critical in the repair of wound injuries and aggressive behavior of tumors, which are mainly performed by the actions of vascular endothelial growth factor (VEGF) and hypoxia-inducible factor-1 (HIF1-α). Pro-inflammatory effects of TF have been reported in asthma, CVDs and viral infections, including COVID-19, which result in tissue hypertrophy, inflammation, and thrombosis. TF-FVII induces angiogenesis via clotting-dependent and -independent mechanisms. Clottingdependent angiogenesis is induced via the generation of thrombin and cross-linked fibrin network, which facilitate vessel infiltration and also act as a reservoir for endothelial cells (ECs) growth factors. Expression of TF in tumor cells and ECs triggers clotting-independent angiogenesis through induction of VEGF, urokinase-type plasminogen activator (uPAR), early growth response 1 (EGR1), IL8, and cysteine-rich angiogenic inducer 61 (Cyr61).